Development Projects of Non-Governmental Organisations towards Social-Economic Welfare in Kisoro Municipality. - Pius, Ngarama (Kabale University, 2020)
The study investigated the contribution of development projects of Non-Governmental Organisations towards social-economic welfare in Kisoro Municipality, Kisoro District. The study was guided by four objectives namely: to identify the various projects carried out by the Non-Governmental Organizations; to establish the ways in which development projects of Non-Governmental Organizations have improved social-economic welfare of the people; to assess the challenges faced by the NGOs in the delivery of social-economic welfare support; and to suggest ways for effective and efficient delivery of social-economic welfare by Non-Governmental Organizations’ development projects in Kisoro Municipality. The study was both qualitative and quantitative in nature. Both simple random sampling and purposive sampling were used to select a total of 143 general and key respondents respectively for the study. The study revealed that (98%) were able to identify the various development projects carried out by NGOs in the study area. Among the development projects included agriculture through empowering the local people with quicker growing crop varieties, better breeds of cattle and goats and supporting poultry farming among others; in addition to promoting and advocating for gender equality where NGOs had invested in boosting the potentials of women in the participation of household, national and international development in many capacities. The study findings also indicated that (99%) acknowledged that development projects carried out by NGOs had improved social economic welfare of the people in the study area. It was concluded that there were challenges encountered by NGOs in the delivery of social economic welfare support to the people in the study area. It was also included that there were measures put in place to the challenges encountered by NGOs in the delivery of social economic welfare support to the people in the study area. The study came up with recommendations among which were that: NGOs should behave in a manner that they can justify or defend; and the need to develop a system for monitoring and evaluating NGOs’ development project work and activities as well as enhancing information and dissemination on the effectiveness of this source of assistance for public good.